THE EFFECT OF SPIRITUAL INTELLIGENCE TO INCREASE ORGANIZATION PERFORMANCE THROUGH WORKERS JOB SATISFACTION - Florentina K Tehubijuluw (Business and Entrepreneurial Review, 2014)
Spiritual intelligence enables people to live with the greater meaning and depth and to look for a meaning beyond the physical needs and a low-level life in their business. Spiritual intelligence will also assist the workers in achieving their happiness and satisfaction with their current jobs.In the long run, spiritual intelligence will help the organizations to achieve business objectives and allow the employees to flourish within the organization. The main objective of this study is to analyze the effect of worker’s spiritual intelligence to achieve organization performance using workers job satisfaction as mediating variable. This study is choosing some management practices in Indonesian biggest developer companies. Respondents in this research consist of workers in all business units owned by those developer companies. All the data is statistically analyzed using the Structural Equation Method model. Findings of this research indicate that there’s a positive effect between spiritual intelligence workers and job satisfaction. The study also proved that as long as the workers satisfied with their jobs, their productivity will increase and finally the organization performance will also improve. The future research should consider the importance role of the leader for organization performance by setting-up core value within organization. This study is the first, to the researcher’s knowledge, to see the effect of all dimensions of spiritual intelligence into workers job satisfaction and finally to improve organization performance.